PENGARUH KOMPETENSI PEGAWAITERHADAP PENERAPAN ELECTRONIC GOVERNMNENT DI DESA TIMORENG PANUA KECAMATAN PANCA RIJANG KABUPATEN SIDENRENG RAPPANG - feby anggunita; Sofyan B; Andi Ilham (PRAJA: Jurnal Ilmiah Pemerintahan, 2020)
The effect of employee competence in Timoreng Panua Village, Panca Rijang District, Sidenreng Rappang Regency,2) to determine the application of electronic government in Timoreng Panua Village, Panca Rijang District, Sidenreng Rappang Regency, and 3) to determine the effect of employee competence on electronic application government in Timoreng Panua Village, Panca Rijang District, Sidenreng Rappang Regency. The population in this study included all family heads consisting of 2 (two) hamlets totaling 574 families. The sampling technique is probability sampling, the member of samples in this study amounted to 85 households. Data collecton technique using of observation, questionnaires, documentation, and interviews. Quantitative data analysis techniques used are frequency distribution analysis and simple linear regression analysis. The result showed that: 1) employee competencies were quite good with an average percentage of 58,3%, 2) electronic government was quite good with an average percentage of 56,9%, 3) employee competence affected the implementation electronic government, this is proven through data output from summary table R2 of 0,603 or 60,3%. T value = 6,881> 1,992 table with significance value of 0,000<0,05. So there is a significant (significant) influence of employee competency variable (X) on electronic government variables (Y) in Timoreng Panua Village, Panca Rijang District,Sidenreng Rappang Regency.